Evaluation of the Effects of Two Dressing Materials: Absorbable Collagen Wound Dressings (HeliCOTE®) and Oxidized Regenerated Cellulose (Surgicel®) on Wound Healing at the Palatal Donor Site after Free Gingival Graft Surgery: A Pilot Study. - Sun, Teresa. (2017)
Abstract: ABSTRACT Aim & Hypothesis: The aim of the study was to evaluate the effects of Absorbable Collagen Wound Dressings (HeliCOTE®) and Oxidized Regenerated Cellulose (Surgicel®) on palatal wound healing rate and pain after free gingival graft surgery using clinical measurements and Visual Analogue Scales (VAS). The hypothesis was faster wound healing would be observed among palatal wounds covered by Absorbable Collagen Wound Dressings (HeliCOTE®) compared with the Oxidized Regenerated Cellulose (Surgicel®) group. Also, compared to Oxidized Regenerated Cellulose (Surgicel®), patients would have less pain when palatal wounds are covered by Absorbable Collagen Wound Dressings (HeliCOTE®). Materials & Methods: 20 patients required FGG surgery were randomly assigned to one of the two experimental groups, the HeliCOTE® group or the Surgicel® group. Dressing materials were applied to the palatal wounds and stabilized by suture. Post surgical photographs were exposed at the day of surgery and post-surgical day 7 and 14 for evaluation of wound healing and the surface area of the remaining wound was calculated by photo-digital planimetry using computer software. Visual Analogue Scales (VAS) was collected at post-surgical day 3 and 7 for pain assessment. Adverse events including post-surgical bleeding, infection and necrosis of the tissue were examined and recorded at post- surgical 7 and 14 days. Following the assessment, comparison between the experimental groups on surface area change of the remaining wound, VAS pain scores and other variables were analyzed. Results: The mean reaming wound area decreased over time for the HeliCOTE® group, however in the Surgicel® group, the mean surface area of the remaining wound increased during first post-surgical week and follow by decreased during second week post-surgically. The mean reduction in remaining wound area was statistically significant greater in the HeliCOTEl® group compared to the Surgicek® group during the first post-surgical week (p= 0.028). The HeliCOTE® group also demonstrated greater reduction of mean remaining wound surface during the second post-surgical week and the overall two-week post surgical period when compared to the Surgicel® group but the difference between two groups was not statistically significant (p= 0.153; p= 0.951.) The mean VAS pain scores showed no statistically significant difference between two experimental groups except one of the question from post-surgical day 3. Conclusions: The result of the present prospective clinical trial showed Absorbable Collagen Wound Dressings (HeliCOTE®) enhanced palatal wound healing when compared with the Oxidized Regenerated Cellulose (Surgicel®) group during the first post-operative week. When the time point reached to the second week the healing rate between two experimental groups became comparable. Patients experienced similar post-operative discomfort when evaluating pain assessment by VAS pain scores. Both dressings did not place patients at a higher risk of infection or other complication, and both dressings were beneficial in achieving hemostasis. Future studies might involve larger sample size, control group without dressing material and histological assessment to further understand the mechanism of action of the dressing materials.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Periodontology.; Advisor: Nadeem Karimbux.; Committee: Bjorn Steffensen, Tannaz Shapurian, and Sarah Pagni.; Keyword: Dentistry.